Empowering Reading Habit of English Fiction Books to Improve English Vocabulary: Evidence from Students in an Indonesian Higher Education - Wahyuningsih, Sri; Ludfiyani, Anif (CV. Tripe Konsultan, 2024)
Low English literacy has a major impact on the education sector. In particular, it has an impact on less qualified human resources. This study aims to explore the students’ perception of reading habits on English fiction books to improve English vocabulary in Indonesian higher education. This study used a qualitative case study method. Data were gathered through semi-structured interviews with four students consisting of two female and two male students from the English Education Department. The results of the study reveal that students believe that reading fiction books can help them memorize English vocabulary, and English fiction books can enrich English vocabulary, especially new words. On the other hand, some challenges appear in reading English fiction books. These include the difficulty of understanding unfamiliar words in English fiction books among male students and the need for sufficient time to read English fiction books completely. Finally, the implication of this study was discussed.